Mobile and Wireless Technology 2015 - Kim, Kuinam J (Springer, 2016)
This book provides a snapshot of the current state-of-the-art in the fields of mobile and wireless technology, security and applications. The proceedings of the 2nd International Conference on Mobile and Wireless Technology (ICMWT2015), it represents the outcome of a unique platform for researchers and practitioners from academia and industry to share cutting-edge developments in the field of mobile and wireless science technology, including those working on data management and mobile security. The contributions presented here describe the latest academic and industrial research from the international mobile and wireless community. The scope covers four major topical areas: mobile and wireless networks and applications; security in mobile and wireless technology; mobile data management and applications; and mobile software. The book will be a valuable reference for current researchers in academia and industry, and a useful resource for graduate-level students working on mobile and wireless technology.